2013
DOI: 10.1039/c2ta01125e
|View full text |Cite
|
Sign up to set email alerts
|

Silica SOS@HKUST-1 composite microspheres as easily packed stationary phases for fast separation

Abstract: Metal-organic frameworks (MOFs) have been investigated for separations including chromatography.Typically, MOF particles are directly packed into columns for the separations. The irregular shapes and wide size distributions of MOF particles have led to difficulty in column packing and low column efficiency or high back pressure. We describe here the preparation of MOF-silica microspheres as packing materials for fast and efficient liquid chromatography. Spheres-on-sphere (SOS) silica particles are prepared, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 72 publications
2
120
0
Order By: Relevance
“…Activated carbons, zeolites, silica and alumina have been evaluated, with well performance only for some cation-free zeolites [7][8][9][10][11][12]. More recently, the preparation and characterization of metal-organic frameworks (MOFs) have opened new opportunities in the search of highly efficient materials for adsorptive separation of light hydrocarbons [3,[13][14][15][16][17]. Practically infinite combinations of metal ions and organic ligands (or building blocks) are available to form porous frameworks with pore topology and surface functionality with potentiality for light hydrocarbons adsorption-based separation.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbons, zeolites, silica and alumina have been evaluated, with well performance only for some cation-free zeolites [7][8][9][10][11][12]. More recently, the preparation and characterization of metal-organic frameworks (MOFs) have opened new opportunities in the search of highly efficient materials for adsorptive separation of light hydrocarbons [3,[13][14][15][16][17]. Practically infinite combinations of metal ions and organic ligands (or building blocks) are available to form porous frameworks with pore topology and surface functionality with potentiality for light hydrocarbons adsorption-based separation.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon indicates that the interaction of the carboxyl groups on the CCSs with Cu 2? in HKUST-1 [10].…”
Section: Characterizationmentioning
confidence: 99%
“…However, the low mechanical strength and block nature of the MOF products greatly prevent their application in these certain areas. To overcome this issue, great efforts have been made on designed synthesis of novel-type composites of MOFs with polymers or nanocarbons in recent years [8][9][10]. For instance, Schwab et al [11] reported the in situ immobilisation of a MOF (HKUST-1) into a hydrophilized macroporous polyHIPE monolith, and revealed that the resulting HKUST-1@polyHIPE composites effectively combines the macroporosity of the polyHIPE with the microporosity of the crystalline MOF of HKUST-1, which is an attractive combination for applications where diffusion processes are limiting.…”
Section: Introductionmentioning
confidence: 99%
“…Silica is the most common stationary phase used in normal phase chromatography and therefore, a natural step forward is to combine silica and MOFs to achieve better performances. Bradshaw's group [8] introduced a sphere-on-sphere (SOS) technique to immobilize small engineered 200 nm silica nanospheres on 5.5 µm silica microspheres. The SOS system with carboxylic groups acted as scaffold for the subsequent growth of HKUST-1 crystals, and the obtained SOS-COOH@HKUST-1 composite ( Fig.…”
Section: Stationary Phases For Separationsmentioning
confidence: 99%
“…These unique features have led researchers to explore combining MOFs with other functional materials to form novel composites with advanced properties [6]. Indeed, ceramics, metal nanoparticles, polymers and biomolecules have been combined with MOFs to afford new materials that have demonstrated unprecedented performance in the areas of catalysis [7], molecular separations [8], sensing [9], plasmonics [10], gas storage [11], controlled guest release [12,13], and protection of biomacromolecules [14]. The most widely studied of these composite systems are based on integrating metal and metal oxide nanoparticles with MOFs.…”
Section: Introductionmentioning
confidence: 99%